Comparison of open surgery and endovascular treatment of asymptomatic juxta/pararenal abdominal aortic aneurysm - Zlatanović, Petar (Medicinski podmladak, 2023)
Endovascular abdominal aortic aneurysm repair (EVAR) has gained widespread acceptance in the treatment of patients with abdominal aortic aneurysm (AAA). The applicability of EVAR is limited by the absence of adequate infrarenal neck or involvement of the visceral arteries, such as in juxtarenal and pararenal AAA (JAAA/PAAA). Current guidelines recommend that elective management of JAAA/PAAA and the choice of different techniques and different options should be considered based on patient status, anatomy, local routines, team expertise, and patient preference. The main advantage endovascular techniques lies in the avoidance of aortic cross clamping and subsequent lower risk of renal dysfunction, less surgical trauma and faster recovery, which may be advantageous for patients at high risk of open surgery. However, recent reports show that JAAA/PAAA patients can be treated in high-volume aortic centres with low short-term mortality and morbidity and good medium- and long-term results that are equal in both groups. Low-surgical-risk patients might benefit from open surgery, while high-risk patients might benefit from endovascular first approach of JAAA/PAAA. This provides useful information to help clinicians and patients choose between the two procedures when both are available.
Keywords: abdominal aortic aneurysm (AAA); juxtarenal AAA (JAAA); pararenal AAA (PAAA); endovascular aneurysm repair (EVAR); open surgical repair (OSR)